A new Canadian inception cohort for juvenile idiopathic arthritis: The Canadian Alliance of Pediatric Rheumatology Investigators Registry. (11th February 2020) - Batthish, Michelle; Berard, Roberta; Cabral, David; Bolaria, Roxana; Chédeville, Gaëlle; Duffy, Ciaran; Gerhold, Kerstin; Gerschman, Tommy; Huber, Adam; Proulx-Gauthier, Jean-Philippe; Rosenberg, Alan; Rumsey, Dax; et al.
Abstract: Objectives: The aim was to describe the design, methods and initial findings of a new Canadian inception cohort of children with JIA, The Canadian Alliance of Pediatric Rheumatology Investigators (CAPRI) JIA Registry. Methods: The CAPRI JIA Registry was started in 2017 to collect information prospectively on children enrolled within 3 months of JIA diagnosis across Canada. The registry has a non-traditional modular design, with no artificially set times for registry visits to occur, streamlined multi-method data collection that requires 2–4 min per visit, and reports cumulative incidence of treatments, outcomes and adverse events calculated by Kaplan–Meier survival methods. Results: A total of 166 patients, enrolled a median of 6 weeks after JIA diagnosis at 10 centres, were included. The median age at diagnosis was 9 years [interquartile range (IQR) 3, 13], 61% were female and 51% had oligoarticular JIA. The median three-variable clinical Juvenile Arthritis Disease Activity Score was 6.5 (IQR 4, 10) at enrolment, and the median time to first attainment of clinically inactive disease (CID) was 24 weeks (by 1 year, 81%). Within 1 year of diagnosis, 70% of patients had started a DMARD and 35% a biologic agent. The rates of adverse events and serious adverse events were 60 and 5.8 per 100 patient-years, respectively. Conclusion: This streamlined and flexible registry minimizes the burden of data collection and interference with clinic operations. Initial findings suggest that treatments for newly diagnosed patients with JIA in Canada have intensified, and now 81% of patients attain CID within 1 year of diagnosis.